Philosophical Approaches to the Foundations of Logic and Mathematics : In Honor of Stanisław Krajewski - Trepczyński, Marcin, (Poznań Studies in the Philosophy of the Sciences and the Humanities ;, 2021)
Eleven papers collected in the volume Philosophical Approaches to the Foundations of Logic and Mathematics address various aspects of the "roots", basic concepts and the nature of logic and mathematics. Taken together, these papers reveal how many serious philosophical problems lie at the foundations of logic and mathematics. The topics discussed in this volume include: transcending anti-foundationalism and two concurrent trends of "anthropological" and "practical" understanding of the foundations of mathematics, new approaches to mathematical realism, the "roots" of logic in a genetic perspective, the primacy of truth or satisfaction, and the "effectiveness" of mathematics in terms of categorical semantics.